Perancangan InteriorLibrary&Co-working Space di Surabaya - Nikko Aditya Perdana; mariana wibowo; filipus priyo suprobo (Intra, 2015)
The development of this advanced age demands that humans should have a vasy majority of extensive knowledge. Library is one of the most accurate and effective information centre, but the truth is, modern societies rely more on the internet that have lower accuracy than the library. Co-working (collaborative working) is a new work style that involves collavorative working environment so as to produce many new opportunities. The concept of the interior design, which combines a library and a work station  with co-working concept is giving a good impact to the circulation, which enables the user to work easier. The more fenceless environment is appearing as well between the users, so that the information can be acquired better. By combining the concepts with their own advantages, it is expected to stimulate the interest in reading, and also to expand relations, as well as increasing productivity in the work field and business in societies, especially in Surabaya.